Supratext in Trans Baikal Business Written Texts of the XVIII Century as a Source of Reconstruction of the Regional Dialect of that Time (Proceedings of Southern Federal University. Philology, 2019)
Alexander P. Mayorov (Ulan-Ude, Russian Federation)The article deals with the prospects of linguistic-source analysis of the supratext as one of the most common structural varieties of monuments of business writing of the XVIII century. Among Trans Baikal written records as sources for reconstruction of regiolect it is distinguished such genre variety of supratext as the investigation of the case, property inventories, resolusion’s magazines.The study was conducted on the material of the Trans Baikal business writing of the XVIII century, and this is the relevance of the topic, since the material of the analyzed supratexts allows to establish the regional status of the used lexical units.Trans Baikal supratexts, thanks to the integrated multi-genre texts, distinguished by the unity of theme and content, a community of referent and of the chronotope, are characterized by diglossia distribution of linguistic resources – common, book-literary words in the official genres (decrees, promemoria, orders, etc.), on the one hand, and national-colloquial, regionally marked words in the request documents and in the registration of genres (objavlenija ‘request’, inventory records, etc.), on the other hand. These linguistic means, correlating with the same reality, are in certain systemic relations with each other.As a result, a comparative analysis of the linguistic content of the texts included in the supratext makes it possible to clarify the lexical meaning of the word; to establish the meaning of the word-hapax; to assess the nature of synonymic relations in words denoting the same denotate; and, most importantly, to determine the regional status of the lexical unit.Key words: regional dialect, regionalism, supratext, Transbaikalian business writing of the XVIII century.DOI 10.23683/1995-0640-2019-3-34-45